2015
DOI: 10.1371/journal.pone.0138684
|View full text |Cite
|
Sign up to set email alerts
|

New Epidemiological and Clinical Signatures of 18 Pathogens from Respiratory Tract Infections Based on a 5-Year Study

Abstract: BackgroundRespiratory tract infections (RTIs) are a heavy burden on society. However, due to the complex etiology of RTIs, the clinical diagnosis, treatment, and prevention of these infections remain challenging, especially in developing countries.MethodsTo determine the epidemiological and clinical characteristics of 18 respiratory pathogens, we analyzed 12,502 patients with acute respiratory infections (ARIs) by performing polymerase chain reaction (PCR) on patient pharyngeal swabs.ResultsSamples positive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
11
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 43 publications
11
11
1
1
Order By: Relevance
“…The detection of MP, PIV, and hMPV was the highest in autumn, summer, and spring, respectively. These results are similar to the findings in Guangzhou, China (14). Nevertheless, a multicenter study conducted in the United States revealed that MP peaked in the winter, and a study conducted in Shenzhen, China, indicated that the detection rate of PIV was highest in autumn (10,15).…”
Section: Discussionsupporting
confidence: 88%
“…The detection of MP, PIV, and hMPV was the highest in autumn, summer, and spring, respectively. These results are similar to the findings in Guangzhou, China (14). Nevertheless, a multicenter study conducted in the United States revealed that MP peaked in the winter, and a study conducted in Shenzhen, China, indicated that the detection rate of PIV was highest in autumn (10,15).…”
Section: Discussionsupporting
confidence: 88%
“…Moreover, our results demonstrated that EV infections occurred between April and September 2015, with the peak detection rate in August 2015, which was in accordance with previous reports [27]. Many studies have shown that EVs are often detected in summer and autumn [27,[31][32][33][34]. We speculate that climate conditions might be an important factor for EV detection in temperate regions.…”
Section: Aris Acute Respiratory Infectionssupporting
confidence: 92%
“…Details of pathogens in single and multiple respiratory infections with influenza-positive cases.Similar findings of single and multiple pathogen coinfections with influenza have been reported from Brazil, Turkey, Japan, and China[29][30][31][32][33][34].To the best of our knowledge, this could be the first study undertaken with multiplex RT-PCR kit on 21 respiratory pathogen for detection of influenza A, A/H1N1, influenza B, RV, RSV A-B, PIV 1-4, coronavirus OC43, NL63, 229E, and HKU1, MPV A-B, BV, Mycoplasma pneumoniae, AV, EV, and PeV. Recently, Rutvisuttinunt et al have reported the detection rate of viral pathogens (71.3%) in specimens of ARI cases collected from South East Asian countries including Nepal.…”
supporting
confidence: 85%